Personality resemblance between parents and offspring: study of five factors across four samples and questionnaires - Bratko, Denis (Array, 2014)
The aim of this study was to compare personality resemblance in four independent Croatian samples using the same family study design, but different measures of five-factor personality traits. The family study design can provide evidence of familial aggregation of personality and of assortative mating. Father-mother correlations, father-offspring correlations, mother-offspring correlations and regressions of offspring on midparent score were computed for five broad personality domains in each sample. Father-mother correlations ranged between −.12 and .27 across different samples and questionnaires, while father-offspring correlations ranged between .04 and .34, mother-offspring correlations between −.01 and .28 and regressions of offspring on midparent scores between .05 and .35. These results are congruent with earlier findings of: (a) low assortative mating for personality, and (b) moderate familial aggregation of personality, which is lower compared to heritability estimates from earlier studies using twin design. Familial aggregation is mostly comparable in size across four different five-factor questionnaires suggesting that, from a behavior genetic perspective, conclusions on family resemblance should not differ depending on the five-factor personality questionnaire used.